The Influence Of Independent Commissioners, Institutional Ownership, and Fiscal Loss Compensation On Tax Avoidance In Health Sector Companies In 2018-2022 - Billa, Naela Andira Salsa; Jannah, Roudlotul; Ramadhan, Khrisnanda Putra Wahyu; Fajarudin, Ibnu (IJEBD (International Journal of Entrepreneurship and Business Development), 2024)
Purpose: This study aims to analyze the effect of independent commissioners, institutional ownership, and fiscal loss compensation on tax avoidance in health sector companies in Indonesia during the 2018-2022 period. This research method is quantitative, using secondary data in the form of financial reports obtained from the official website of the Indonesia Stock Exchange. The sample used was 14 companies using purposive sampling method. The data analysis method used is multiple linear regression analysis method by conducting several tests. The results of this study indicate that independent commissioners, institutional ownership, and fiscal loss compensation have a negative and insignificant effect on tax avoidance. Design/methodology/approach: Quantitative research method using multiple linear regression analysis method. Findings: Independent commissioners significantly do not affect Tax Avoidance in health sector companies in 2018-2022. Institutional ownership significantly does not affect Tax Avoidance in health sector companies in 2018-2022. Fiscal loss compensation significantly does not affect Tax Avoidance in health sector companies in 2018-2022. Paper type: Research Paper